Effects of toroidal rotation shear and magnetic shear on thermal and particle transport in plasmas with electron cyclotron heating on JT-60U. (15th June 2015) - Yoshida, M.; Honda, M.; Narita, E.; Hayashi, N.; Urano, H.; Nakata, M.; Miyato, N.; Takenaga, H.; Ide, S.; Kamada, Y.
Abstract: Increases in thermal and particle transport with electron cyclotron heating (ECH) that are observed in many tokamaks can be a critical issue in establishing ITER operational scenarios with electron heating. To address the issues, conditions with no increase in the thermal and particle transport with ECH have been experimentally investigated in positive magnetic shear, weak magnetic shear (WS) and reversed magnetic shear plasmas with internal transport barrier in the ion channel. The ion heat diffusivity ( χ i ) around the internal transport barrier in the ion temperature remains constant with ECH when a large negative toroidal rotation shear (|d V φ /d r | > 4 × 10 5  s −1 ) is formed before the ECH. On the other hand, χ i increases on the condition that the toroidal rotation shear is small or positive. The characteristics do not depend on magnetic shear, the electron to ion temperature ratio ( T e / T i ) and ECH power. The electron heat diffusivity stays constant with ECH when the magnetic shear is negative. Effective particle transport remains constant or reduces during ECH under the condition of negative magnetic shear. An observation indicates that there is no threshold of the negative magnetic shear or a very small one for the electron channel sustainment; the electron thermal and particle confinement is maintained during ECH with a small negative magnetic shear in the WS operation.